Enantioselective Cascade Reaction for Synthesis of Quinolinones through Synergistic Catalysis Using Cu–Pybox and Chiral Benzotetramisole as Catalysts - Lu, Xuehe; Ge, Luo; Cheng, Cang; Chen, Jie; Cao, Weiguo; Wu, Xiaoyu (Chemistry : a European journal, 2017)
In contrast to the well‐studied asymmetric catalyzed synthesis of tetrahydroquinolines, the asymmetric methodologies toward 3,4‐dihydroquinolin‐2‐ones are quite rare. Herein, the first asymmetric cascade reaction is reported between ethynyl benzoxazinanones and mixed‐anhydrides generated from aryl acetic acids and pivaloyl chloride, based on synergistic catalysis. This allowed the formation of attractive 3,4‐dihydroquinolin‐2‐ones bearing two vicinal chiral centers at C3 and C4 in high yields with excellent diastereo‐ and enantioselectivities. A plausible chiral induction model for this reaction was proposed. The utility of this methodology was exemplified by further elaboration of the cyclization products by removal of the N‐protecting groups. Synergistic catalysis: An asymmetric cascade reaction synergistically catalyzed by a Cu–Pybox complex and a benzotetramisole‐type Lewis‐base catalyst is developed, affording 3,4‐dihydroquinolin‐2‐ones bearing two vicinal chiral centers in high yields with excellent stereoselectivities.